Danish literature as World literature - Ringgaard, Dan 1963-; Thomsen, Mads Rosendahl 1972- (Literatures as World Literature, 2017)
"Despite being a minor language, Danish literature is one of the world's most actively translated, and the Scandinavian state is the home of a number of significant writers. Hans Christian Andersen remains one of the most translated authors in the world, philosopher Søren Kierkegaard inspired modern Existentialism, Karen Blixen chronicled her life in colonial Kenya as well as writing imaginary, cosmopolitan tales, and the writers among the circles of literary critic Georg Brandes in the late 19th century were especially important to the further development of European Modernism. Danish Literature as World Literature introduces key figures from 800 years of Danish literature and their impact on world literature. It includes chapters devoted to post-1945 literature on beat and systemic poetry as well as the Scandinavia noir vogue that in both crime fiction and cinema. "--